Examining YouTube Videos with Counting and Numbers Content for Preschool Children - ŞENGİL AKAR, Şeyma (Institute of Education Sciences, Eskisehir Osmangazi University, 2023)
Children, who are introduced to technology as soon as they are born, have access to internet-based videos as young as one year old. These colourful, animated cartoon/animation content supported by songs have turned into informal learning tools for children. Some of these videos, which families do not hesitate to present as educational content, are math videos. These videos reach millions of views. These videos with mathematical content prepared for children, mostly shared with the label of children's songs, are the subject of this study. In this study, we focused on Turkish number and counting videos from the open access YouTube content provider. Document analysis method was used in this study. As a result of the analysis, it was observed that only a few videos were adequate in terms of mathematical language, content and number teaching, and almost all of the other videos included incorrect or inaccurate mathematical representations. While counting, it was observed that number symbols were used as "ordinal numbers". In addition, it was observed that there were scenes where the amount counted and the number did not match. It was thought that these situations could lead to false learning. Based on all these findings, it can be concluded that the mathematical language used in YouTube video content is weak.
Keywords: Okul Öncesi Eğitim; Early Childhood Education; Mathematics Education; Matematik Eğitimi; Numbers; counting; early childhood; YouTube; video content; 4. Education